Towards sophisticated control of robotic manipulators - Iqbal, Jamshed (Strojniški vestnik, 2015)
Robotic manipulators have reshaped industrial processes. The scientific community has witnessed an ever increasing trend in robots deployed to accomplish various tasks in industry. The complex nature and constrained requirements of robots may demand non-trivial control approaches. This paper deals with the design, simulation and hardware realization of two sophisticated control strategies: computed torque control (CTC) and variable structure control (VSC) on a pseudo-industrial manipulator with six degrees of freedom (DOF). Based on the derived kinematic and dynamic models of the robot, control laws have been formulated, which are then subjected to various test inputs in a simulation to characterize the tracking performance. The simulation results were then validated by implementing control laws on a custom-developed pseudo-industrial autonomous articulated robotic educational platform (AUTAREP). The experimental results show the effectiveness of the control strategies to track a desired trajectory.
Keywords: industrijski roboti; krmiljenje z variabilno strukturo (VSC); manipulatorji; računsko krmiljenje navora (CTC); robotsko krmiljenje; robustni zakoni; šest prostostnih stopenj